Menganalisis Kebutuhan Pembelajaran Bahasa Jerman dengan Tema Schule (Sekolah) - Sitinjak, Febyola Angelika; Nainggolan, Laura Hotmauli; Lumbantobing, Naomi Octa M.; Hutagalung, Shennyin Sella Ester Octavia; Hutagalung, Surya Masniari (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Learning German in schools requires materials tailored to students' needs to ensure optimal learning. Therefore, a learning needs analysis is a crucial step in determining appropriate materials, media, and methods. This study aims to examine German language learning needs, focusing on school themes. The method used was a qualitative descriptive approach, with data collection through literature reviews from various journals related to German language learning. The results indicate that German language learning needs to emphasize several key aspects: vocabulary mastery (Wortschatz), language structure (Grammatik), and communicative expressions (Redemittel), relevant to students' lives in the school environment. Furthermore, students need engaging, interactive, and easily accessible learning materials and media, such as through digital media or smartphones. Therefore, learning materials that are contextual and relevant to students' daily lives can help improve their understanding and motivation to learn German. This learning needs analysis serves as an important foundation for developing more effective teaching materials and media tailored to student characteristics.